Registration of the transfer of land rights as a result of an inckracht court decision at the Tegal City land office - Kurniawati, Yanuari Ulfah; Silviana, Ana (Gema Wiralodra, 2023)
The registration of the transfer of land rights resulting from court decisions is an unusual transitional registration, so it is necessary to study what decisions can be used as the basis for registering rights and what the registration mechanism is. An example is the decision of the Tegal District Court No. 01/Pdt.G/2013/PN.Tgl. which has permanent legal force so that it can be used as the basis for registration of the transfer of rights. The registration mechanism is through a review and recommendation from the Tegal City Land Office, followed by ownership registration.